MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN ALAT PERAGA PADA MATA PELAJARAN IPA KELAS IV SDN NOMOR 14 SIMBOLON PURBA - Pindo Hutauruk; Rinci Simbolon (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to determine the improvement of learning outcomes and implementation of learning by using props. The location of the research was conducted at SDN No 14 Simbolon Purba Palipi Subdistrict Samosir District with the subject of research is the fourth grader of 20 people. Data collection techniques used are tests and observation sheets. Based on the results of the analysis can be concluded that there is an increase in learning outcomes using visual aids in science lesson material Framework man and its function in the fourth grade students SDN No. 14 Simbolon Purba Academic Year 2017/2018.Keywords: Learning outcomes, Props.